TRADISI LOFU-LOFU DALAM PERNIKAHAN DI NEGERI YAPUTIH KECAMATAN TEHORU KABUPATEN MALUKU TENGAH: (Studi Tentang Nilai-Nilai Pendidikan Islam) - Umarella, Samad; Zain, Humairatuzzahro (al-Iltizam: Jurnal Pendidikan Agama Islam, 2024)
The Lofu-lofu tradition in marriage ceremonies in Yaputih is a cultural practice carried out by the people of Yaputih for decades as an effort to preserve and maintain the Lofu-lofu tradition. This tradition is practiced during marriage ceremonies and is intended to strengthen social bonds among community members. Furthermore, this tradition is preserved because it embodies Islamic educational values, which have sustained its relevance to this day. This study adopts a qualitative research methodology, employing data collection techniques such as observation, interviews, and documentation. Data analysis is conducted through the following steps: data reduction, data analysis, and conclusion drawing, with the researcher acting as the primary instrument. The findings of this study indicate that marriage ceremonies in Yaputih are conducted in accordance with Islamic teachings, while incorporating customary practices or traditions. The marriage process includes several stages: the proposal, the wedding ceremony, and the final stage, known as gulung tikar (literally "rolling the mat"). Throughout the implementation of these ceremonies, several Islamic educational values are observed, including the values of strengthening kinship (silaturahmi), charity (sedekah), mutual assistance (tolong-menolong), worship (ibadah), and respect for parents.